A descriptive study of current practices and procedures of selected laundry shops in Makati Central Business District - Alegre, Levi S.; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT This research is a descriptive study of present practices and procedures in the laundry shop industry from the points of view of selected laundry shop owners and consumers. The study intended to determine the motivations of business owners in setting up laundry shops, describe the procedures utilized in laundry shops, identify the problems they encountered and how these were resolved. This study also determined the motivations of consumers in availing laundry services, identified the consumers' common practices, problems encountered and how these were resolved and determined the consumers' expectations and demands from the laundry shops. Using convenience sampling method, the study selected 12 laundry shop owners and 60 consumers in Makati Central Business District to answer survey questionnaires. The study revealed 75% of the laundry shops have been in the business for more than 10 years, 58% are operating a pick-up station setup with one to two personnel and five are one-stop laundry shops. All had basic in-house training and knowledge on laundry processes. Problems that they encountered were mixed up laundry, damaged clothes and missing items. For such cases, laundry shop owners pay for the damages. Convenience was the main reason why 60% of the consumers avail of laundry shop[ services; 56 of them visit the laundry shop once a week and 24 of them use laundry services for more than six years now. The study showed that 45 out of 60 consumers bring in their laundry unsorted. Whenever problems were encountered, 42% of consumers immediately call the attention of the owner or the manager who addresses their concerns. Further studies related to this subject matter may be about the quality control guidelines and operation guidelines for laundry shop owners that can aid them in running the laundry business efficiently.
Thesis (Bachelor of Science in Clothing Technology)---University of the Philippines Diliman.
Keywords: Laundry industry -- Philippines -- Makati